Respuesta :
Answer:
A
Step-by-step explanation:
The average rate of change of f(x) in the closed interval [a, b ] is
[tex]\frac{f(b)-f(a)}{b-a}[/tex]
Here [ a, b ] = [ 2, 6 ], thus
f(b) = f(6) = - [tex]2^{6}[/tex] + 70 = - 64 + 70 = 6
f(a) = f(2) = - 2² + 70 = - 4 + 70 = 66
average rate of change = [tex]\frac{6-66}{6-2}[/tex] = [tex]\frac{-60}{4}[/tex] = - 15 → A
Answer:
-15
Step-by-step explanation:
15 is the average rate of change for ƒ(x) = −2x + 70 over the interval 2 ≤ x ≤ 6.
ƒ(b) − ƒ(a)
b − a
=
ƒ(6) − ƒ(2)
6 − 2
=
6 − 66
4
=
−60
4
= −15